Benefits of compression garments worn during handball-specific circuit on short-term fatigue in professional players - Ravier, G.; Bouzigon, R.; Beliard, S.; Tordi, N.; Grappe, F. (The Journal of Strength and Conditioning Research, 2018)
The purpose of this study was to investigate the benefits of full-leg length compression garments (CGs) worn during a handball-specific circuit exercises on athletic performance and acute fatigue-induced changes in strength and muscle soreness in professional handball players. Eighteen men (mean ± SD: age 23.22 ± 4.97 years; body mass: 82.06 ± 9.69 kg; height: 184.61 ± 4.78 cm) completed 2 identical sessions either wearing regular gym short or CGs in a randomized crossover design. Exercise circuits of explosive activities included 3 periods of 12 minutes of sprints, jumps, and agility drills every 25 seconds. Before, immediately after and 24 hours postexercise, maximal voluntary knee extension (maximal voluntary contraction, MVC), rate of force development (RFD), and muscle soreness were assessed. During the handball-specific circuit sprint and jump performances were unchanged in both conditions. Immediately after performing the circuit exercises MVC, RFD, and PPT decreased significantly compared with preexercise with CGs and noncompression clothes. Decrement was similar in both conditions for RFD (effect size, ES = 0.40) and PPT for the soleus (ES = 0.86). However, wearing CGs attenuated decrement in MVC (p < 0.001) with a smaller decrease (ES = 1.53) in CGs compared with regular gym shorts condition (-5.4 vs. -18.7%, respectively). Full recovery was observed 24 hours postexercise in both conditions for muscle soreness, MVC, and RFD. These findings suggest that wearing CGs during a handball-specific circuit provides benefits on the impairment of the maximal muscle force characteristics and is likely to be worthwhile for handball players involved in activities such as tackles.